ANALISIS TINGKAT PENCEMARAN AIR BAWAH TANAH DENGAN METODE GEOLISTRIK DI TPA RUM BALIBUNGA KOTA TIDORE - Aslan, Nasrun; Nagu, Nani; Achmad, Rahim; Ahadian, Erdward Rizky (Fakultas Teknik Universitas Khairun, 2024)
Groundwater is a vital resource for irrigation, industry and drinking water, yet its widespread utilization is causing shortages in many areas. Therefore, it is important to maintain and protect groundwater resources for their sustainability. One way to monitor groundwater pollution is by using geoelectric methods. This study aims to analyze underground water pollution around the Balibunga Rum Landfill and model leachate water flow using geoelectric methods. This quantitative study collected resistivity data on the first pass, which showed resistivity values ranging from 12.5 - 80.7 Ωm to 3366 - 8555 Ωm at a depth of 1.25 m to 19.78m. From the analysis, pollution due to leachate seepage into the ground was identified. The movement of this contamination is towards the area with the lowest elevation, indicating contamination of the groundwater around the landfill.